Poprava, rekristalizacija in rast zrn v jeklu z 2% Si - 0,3% Al - 0,003% C - Steiner Petrovič, Darja (Kovine zlitine tehnologije, 1995)
The decarburized and undecarburized cold rolled electrical steels were annealed in a deoxidized lead bath in the temperature range from 550 to 800°C. The microstructure was examined and the average grain size assesed. The process of recovery was investigated on specimens annealed at lower temperatures by hardness measurements. Industrially manufactured samples of non-oriented sheets were used as comparison.
Keywords: jeklo; elektropločevina; rekristalizacija; rast zrn; mikrosruktura